Seeing the trees for the (urban) forest: more-than-human geographies and urban greening. Issue 2 (2nd April 2020) - Phillips, Catherine; Atchison, Jennifer
ABSTRACT: Urban spaces have long been places to think through human relationships with nature. The recent shift in thinking from urban green space as outcome to urban greening as a process provides an opportunity to consider more explicitly how we engage with more-than-human worlds in urban spaces, in more differentiated ways, and for what ends. In this paper we contribute to growing interest in improved urban sustainability and well-being by bringing human geography perspectives on more-than-human worlds into conversation with the literature on urban greening. Drawing on key examples oriented around urban trees, we consider two main themes: sensibilities and belonging. We argue for an understanding of urban places as collective achievements that not only involve knowing and living with diverse humans and non-humans but also involve the re/making of sensibilities and belongings. Through this paper, we aim to open dialogue about how more-than-human geographies might help us to differently understand urban trees, contemporary urban greening, and people–plant relations.